Education of refugee students in Greece : teachers’ experiences - Marmaridou, Margarita (2019)
Greece encountered an unparalleled flow of people in 2015, what has been described as a “refugee crisis”. A substantial proportion of the refugee population comprised of children under the age of 18. The Greek state has been called to provide these children with the fundamental right to education. Considering that the need for refugee education provision at such a large scale has been recent and abrupt within the Greek context, the present study attempted to explore the experiences of educators involved in this educational project. Semi-structured interviews were conducted with teachers and members of school staff in June 2018 at four different schools in Northern Greece. Three of the schools were located in a small town; the refugee students were integrated in each school through Reception Classes. The fourth school was an Intercultural primary school, located in a big urban centre; the two refugee students attending were integrated into mainstream classrooms. The findings elicited from the interviews manifest differences between the two settings, namely the Reception Classes and Intercultural School, in terms of the challenges faced and the support networks the informants had access to. Linguistic and behavioural issues as well as inadequate support were repetitive themes among Reception Class teachers. The findings indicate the multiple layers and system interconnections that exert influence on the reality facing refugees at host communities. Systems that refugees are involved in or systems over which they possess little to no power all have an impact on their educational experience.